Menaturalisasi Kekuasaan dan Resistensi: Mitos Politik dalam Macapat Jawa Uran-uran “Semut Ireng” - Fauziyah, Naisaa Sanna; Purnomo, Sucipto Hadi; Zustiyantoro, Dhoni (Jurnal Bahasa dan Sastra, 2026)
Previous studies on tembang macapat have generally focused on moral, cultural, and educational values. However, research that positions tembang macapat as a  as a medium of political representation and contique remains limited. Therefore, this study fills this gap by analyzing the uran-uran Semut Ireng as a symbolic reflection of the socio-political dynamics of Javanese society. This analysis employs Roland Barthes’ semiotic theory, which examines tembang through poetic structures by analyzing the meanings of the lyrics at three levels: denotative, connotative, and myth namely the second level of marking that displays the ideology of power and leadership as if it were something natural.. Adopting a qualitative descriptive design, the study analyzes transcribed and translated lyrics of uran-uran Semut Ireng taken from selected YouTube performances. The analysis identifies signifiers and signifieds in each line, then reconstructs their denotative, connotative, and mythological meanings to explain how the song functions as a medium for political messaging. The results indicate that semut ireng represents the common people who possess the courage to voice criticism, while the ideal leader is portrayed through Javanese leadership values that uphold justice and political balance. The study shows how past socio-political realities are rearticulated in uran-uran Semut Ireng, making it relevant today as a medium of reflection and socio-political criticism grounded in local wisdom.